ANALISIS PERLINDUNGAN HUKUM TERHADAP KURIR PADA KASUS WANPRESTASI CASH ON DELIVERY (COD) DALAM PERJANJIAN JUAL BELI DI E-COMMERCE SHOPEE - Dashilfa Afifah; Laras Medina Pranitiaz; Imelda Arthameisia Manullang; Nina Fitria Sukma; Raisha Tiara Hasnakusumah; Dwi Aryanti Ramadhani (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Technological advances facilitate trade. The transaction process can be done without meeting in person so that its coverage becomes unlimited. Online commerce (e-commerce) is regulated by Act No. 19 of 2016 amending Law No. 11 of 2008 on Electronic Information and Transactions as well as in Article 1320 of the Covenant. In the execution of the sale in e-commerce there must be a violation of both the seller and the buyer in particular on the payment system Cash on Delivery (COD). There is legal protection to the courier in the face of a buyer who has committed a misconduct by refusing the goods he ordered. This study uses normative jurisprudence methods by studying and analyzing library materials, legislative regulations, journals, books, and relevant legal research through a statute approach along with a case approach. The results of the research have shown that the legal position of the courier is as a recipient of payment that is responsible for replacing the company of goods delivery services in the exercise of authority of the seller and as a receiver of payment from the buyer.